Supplementation of Mineral-Vitamin Complex in Ration of Growth Performance Boar Crossbreed Age 2-6 Months - I K. A., Rusmawan; Siti, N. W.; Bidura, I G. N. G. (Jurnal Peternakan Tropika, 2018)
This study aims to determine the effect of mineral-vitamin complex supplementation in the ration to growth performance boar crossbreed the age of 2-6 months. The design used was a randomized block design (RBD) comprising 3 treatments and 4 groups as replication, clustering based on weight. The treatments were attempted diets without supplementation of mineral-vitamin complex as the control (A), the diets with 0.10% mineral supplementation-vitamin complex (B), and 0.20% diets supplemented mineral-vitamin complex (C). The variables measured were final body weight, weight gain, feed intake and feed conversion ratio. The results showed that supplementation of mineral-vitamin complex at the level of 0.10% and 0.20% (P <0.5) can improve the final body weight, weight gain and feed efficiency in use but not significantly (P> 0.5) increases feed intake in pigs race crosses the age of 2-6 months. It was concluded that supplementation of 0.10 to 0.20% mineral-complex vitamins in the ration can increase the final body weight, weight gain and feed efficiency in the use of the boar cross breed. Key words:    supplementation, pig cr ossbreeds, carcass production, mineral-vitamin complex